Apoptosis induced in CD4+ cells expressing gp160 of human immunodeficiency virus type 1. - Lu, Y Y (1994)
In a previous study (Y. Koga, M. Sasaki, H. Yoshida, H. Wigzell, G. Kimura, and K. Nomoto, J. Immunol. 144:94-102, 1990), we demonstrated that the expression of gp160, a precursor form of envelope glycoprotein of human immunodeficiency virus type 1, in CD4+ cells causes the downregulation of surface CD4 and single-cell killing by forming intracellular gp160-CD4 complex. In the present study we investigated the events that lead to cell death in CD4+ cells expressing gp160. We found that apoptosis is induced in cells undergoing single-cell death. Moreover, even the cell clone, which expresses so little gp160 that it does not exhibit any apparent cytopathic effects, such as the inhibition of cell growth, was found to be highly susceptible to the apoptosis induction by the anti-Fas monoclonal antibody.